Structural information in therapeutic peptides: Emerging applications in biomedicine - Valentín Iglesias; Oriol Bárcenas; Carlos Pintado‐Grima; Michał Burdukiewicz; Salvador Ventura (FEBS Open Bio)
Peptides are attracting a growing interest as therapeutic agents. This trend stems from their cost‐effectiveness and reduced immunogenicity, compared to antibodies or recombinant proteins, but also from their ability to dock and interfere with large protein–protein interaction surfaces, and their higher specificity and better biocompatibility relative to organic molecules. Many tools have been developed to understand, predict, and engineer peptide function. However, most state‐of‐the‐art approaches treat peptides only as linear entities and disregard their structural arrangement. Yet, structural details are critical for peptide properties such as solubility, stability, or binding affinities. Recent advances in peptide structure prediction have successfully addressed the scarcity of confidently determined peptide structures. This review will explore different therapeutic and biotechnological applications of peptides and their assemblies, emphasizing the importance of integrating structural information to advance these endeavors effectively.